Glycine-spacers influence functional motifs exposure and self-assembling propensity of functionalized substrates tailored for neural stem cell cultures - Taraballi, Francesca; Natalello, Antonino; Campione, Marcello; Villa, Omar; Doglia, Silvia M.; Paleari, Alberto; Gelain, Fabrizio (Frontiers in Neuroengineering, 2010)
The understanding of phenomena involved in the self-assembling of bio-inspired biomaterials acting as three-dimensional scaffolds for regenerative medicine applications is a necessary step to develop effective therapies in neural tissue engineering. We investigated the self-assembled nanostructures of functionalized peptides featuring four, two or no glycine-spacers between the self-assembly sequence RADA16-I and the functional biological motif PFSSTKT. The effectiveness of their biological functionalization was assessed via in vitro experiments with neural stem cells and their molecular assembly was elucidated via atomic force microscopy, Raman and FTIR spectroscopy. We demonstrated that glycine-spacers play a crucial role in the scaffold stability and in the exposure of the functional motifs. In particular, a glycine-spacer of four residues leads to a more stable nanostructure and to an improved exposure of the functional motif. Accordingly, the longer spacer of glycines, the more effective is the functional motif in both eliciting neural stem cells adhesion, improving their viability and increasing their differentiation. Therefore, optimized designing strategies of functionalized biomaterials may open, in the near future, new therapies in tissue engineering and regenerative medicine.